Strengthening The Community Economy Of Hajosari II Sub-District Medan Amplas Through Training On Household Waste Management - Ridho, Hatta; Thamrin, Muhammad Husni; Nasution, Faiz Albar (Talenta Publisher, 2020)
Like other major cities, Medan is also one of the cities that has serious problems related to waste management. Waste management done so far is a standard method that relies only on garbage disposal from temporary shelters to landfills. Thus, utilizing waste in households into products that have economic value, as an alternative step to increase the volume of waste in urban areas. The purpose of this service is to provide skills to the community of Harjosari II Subdistrict of Medan Amplas to manage waste in order to become healthy charcoal briquettes. Methods used in devotional activities include; methods of lectures, practice/training and question and answer questions. The results of community service showed that the community of Harjosari II could attend this training well. Through this training, the people of Harjosari II have the skills to make healthy charcoal briquettes by utilizing organic waste as the main ingredient. Thus, the trainees hoped for intensive assistance to produce healthy charcoal briquettes, in order to increase the income of families who are getting worse in the midst of the Covid-19 pandemic.